A simple and efficient strategy for cell‐based and cell‐free‐based therapies in acute liver failure: hUCMSCs bioartificial liver - Lei Feng; Yi Wang; Yu Fu; Adilijiang Yimamu; Zeyi Guo; Chenjie Zhou; Shao Li; Linya Zhang; Jiasheng Qin; Shusong Liu; Xiaoping Xu; Zesheng Jiang; et al. (Wiley, 2023)
Abstract Acute liver failure (ALF) is a life‐threatening condition. Cell‐based and cell‐free‐based therapies have proven to be effective in treating ALF; however, their clinical application is limited by cell tumorigenicity and extracellular vesicle (EV) isolation in large doses. Here, we explored the effectiveness and mechanism of umbilical cord mesenchymal stem cells (hUCMSCs)‐based bioartificial liver (hUCMSC‐BAL), which is a simple and efficient strategy for ALF. D‐galactosamine‐based pig and mouse ALF models were used to explore the effectiveness of hUCMSC‐BAL and hUCMSC‐sEV therapies. Furthermore, high‐throughput sequencing, miRNA transcriptome analysis, and western blot were performed to clarify whether the miR‐139‐5p/PDE4D axis plays a critical role in the ALF model in vivo and in vitro. hUCMSC‐BAL significantly reduced inflammatory responses and cell apoptosis. hUCMSC‐sEV significantly improved liver function in ALF mice and enhanced the regeneration of liver cells. Furthermore, hUCMSC‐sEV miRNA transcriptome analysis showed that miR‐139‐5p had the highest expression and that PDE4D was one of its main target genes. The sEV miR‐139‐5p/PDE4D axis played a role in the treatment of ALF by inhibiting cell apoptosis. Our data indicate that hUCMSC‐BAL can inhibit cytokine storms and cell apoptosis through the sEV miR‐139‐5p/PDE4D axis. Therefore, we propose hUCMSC‐BAL as a therapeutic strategy for patients with early ALF.